Między ortodoksją a monofizytyzmem. Obsada tronów patriarszych Konstantynopola, Aleksandrii, Antiochii i Jerozolimy w polityce cesarza Zenona - Leszka, Małgorzata B. (Vox Patrum, 1998)
This article is devoted to the problem of emperor Zeno's policy towards the appointment of Constantinople, Alexandria, Antioch and Jerusalem patriarchs to their posts.